A view on abstract and extensibles types - Figueiredo, Lucília; Camarão, Carlos (Revista Colombiana de Computación, 2002)
This paper presents a type declaration construct which provides either a type synonym, a datatype, an abstract type with views, a subtype of an existing type, or a module (collection of declarations), in the style of modern functional programming languages ahich provide support for parametric polymorphism.